Ethnomedicinal plant knowledge of the Karen in Thailand - Methee Phumthum (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. The Thai Karen, the largest hill-tribe in Thailand, guard substantial ethnomedicinal plant knowledge, as documented in several studies that targeted single villages. Here, we have compiled information from all the reliable and published sources to present a comprehensive overview of the Karen ethnomedicinal plant knowledge. Our dataset covers 31 Karen villages distributed over eight provinces in Thailand. We used the Cultural Importance Index (CI) to determine which species were the most valuable to the Karen and the Informant Consensus Factor (ICF) to evaluate how well distributed the knowledge of ethnomedicinal plants was in various medicinal use categories. In the 31 Karen villages, we found 3188 reports of ethnomedicinal plant uses of 732 species in 150 plant families. Chromolaena odorata, Biancaea sappan, and Tinospora crispa were the most important medicinal plants, with the highest CI values. The Leguminosae, Asteraceae, Zingiberaceae, Euphorbiaceae, Lamiaceae, Acanthaceae, Apocynaceae, and Menispermaceae were the families with the highest CI values in the mentioned order. A high proportion of all the 3188 Karen use reports were used to treat digestive, general and unspecified, musculoskeletal, and skin disorders.